'All In': a pragmatic framework for COVID‐19 testing and action on a global scale. Issue 6 (27th May 2020) - Pettit, Syril D; Jerome, Keith R; Rouquié, David; Mari, Bernard; Barbry, Pascal; Kanda, Yasunari; Matsumoto, Mineo; Hester, Susan; Wehmas, Leah; Botten, Jason W; Bruce, Emily A
Abstract : Current demand for SARS‐CoV‐2 testing is straining material resource and labor capacity around the globe. As a result, the public health and clinical community are hindered in their ability to monitor and contain the spread of COVID‐19. Despite broad consensus that more testing is needed, pragmatic guidance toward realizing this objective has been limited. This paper addresses this limitation by proposing a novel and geographically agnostic framework (the 4Ps framework) to guide multidisciplinary, scalable, resource‐efficient, and achievable efforts toward enhanced testing capacity. The 4Ps (Prioritize, Propagate, Partition, and Provide) are described in terms of specific opportunities to enhance the volume, diversity, characterization, and implementation of SARS‐CoV‐2 testing to benefit public health. Coordinated deployment of the strategic and tactical recommendations described in this framework has the potential to rapidly expand available testing capacity, improve public health decision‐making in response to the COVID‐19 pandemic, and/or to be applied in future emergent disease outbreaks. Abstract : This paper proposes a novel 4Ps Framework (Prioritize, Propagate, Partition, and Provide) to guide multidisciplinary, scalable, resource‐efficient, and achievable efforts towards enhanced SARS‐CoV‐2 testing capacity and improved public health decision‐making in response to the COVID‐19 pandemic.